Multifarious characteristics of sulfur-oxidizing bacteria residing in rice rhizosphere - Nyamath, Syed; Subburamu, Karthikeyan; Kalyanasundaram, Geetha Thanuja; Balachandar, Dananjeyan; Suresh, Meena; Anandham, Rangasamy (Folia microbiologica, 2024)
Sulfur-oxidizing bacteria (SOB) are versatile microorganisms known for their ability to oxidize various reduced sulfur compounds, namely, elemental sulfur (S0), hydrogen sulfide (H2S), tetrathionate (S4O62-), and trithionate (S3O62-) to sulfate (SO42-). In this study, out of twelve SOB isolates from rice rhizosphere, five were screened based on their sulfur oxidation potential, viz., SOB1, SOB2, SOB3, SOB4, and SOB5, and were identified as Ochrobactrum soli SOB1, Achromobacter xylosoxidans SOB2, Stenotrophomonas maltophilia SOB3, Brucella tritici SOB4, and Stenotrophomonas pavanii SOB5, respectively. All the isolates displayed chemolithotrophic nutritional mode by consuming thiosulfate and accumulating trithionate and tetrathionate in the growth medium which is ultimately oxidized to sulfate. The strains were authenticated with the production of thiosulfate oxidizing enzymes such as rhodanese and sulfite oxidase. Despite their tendency to oxidize reduced sulfur compounds, B. tritici SOB4 and S. pavanii SOB5 were also found to possess phosphate and zinc solubilization potential, acetic acid, and indole acetic acid (IAA) production and 1-aminocyclopropane-1-carboxylate (ACC) deaminase activity. The presence of sulfanyl (R-SH) groups was noticed in the A. xylosoxidans SOB2. Elemental sulfur conversion into sulfate was noted in the S. maltophilia SOB3, and hydrogen sulfide conversion into sulfate was observed in the Ochromobacter soli SOB1. Sulfur oxidation potential coupled with beneficial properties of the isolates widen the knowledge on SOB.
Keywords: sloučeniny síry; Bacteria; oxidace-redukce; síra; thiosírany; Hydrogen Sulfide; Thiosulfates; sírany; Sulfur Acids; Sulfur Compounds; rýže (rod); Sulfates; Rhizosphere; Sulfur; rhizosféra; sulfan; Oryza; kyseliny síry; Oxidation-Reduction